RESILIENCES TYPES OF KAJEN PESANTREN STRUGGLING COVID 19 PANDEMICS - Fathimatuz Zahra (Kopertais Wilayah X Jawa Tengah, 2022)
Covid 19 is a virus that is evenly distributed among all groups, including Islamic boarding schools in Indonesia. Many of these Islamic boarding schools have been affected by Covid 19, one of which is the Pesantren in Kajen Pati, Central Java. In July 2020, the first positive covid patients from Islamic boarding schools began to appear in the Kajen Pati area. The emergence of covid patients from these pesantren raises pros and cons regarding whether Covid 19 is real or fictitious. As well as various disaster mitigation problems stemming from the resilience of the pesantren in dealing with Covid 19.This research uses methods of interview and internal social media groups discussion. This research, consists of interviewing head of Satgas Covid Santri, Forum Komunikasi Pengasuh Pesantren Kajen (FKPPK), Nyai, Santri and also neighbourhood of Pesantren. How they’re was interpreting of covid 19, how they solving problems and then how they make resiliences between them. Because of Pesantren in Kajen is more about fifty pesantren and also their location was risky for spreading covid 19.This research finding was formulated that’s was the pesantren community's unpreparedness that this covid could affect them. Based on this research, the pesantren resiliences community is divided into believing and being aware that Covid exists, believing but resigning that those affected by Covid are according to God's will, considering that Covid is fictitious and only a conspiracy against Muslims.